Louisa May Alcott house, Louisburg Square, n.d. - Halliday Historic Photograph Company (Tufts Archival Research Center, 2005)
Street-level view of Louisa May Alcott's house in Louisburg Square. This undated image is of the brick homes, seasonal wreaths are displayed in some windows. Note the ironwork fences and rails. A street light is on the right side of the image. 7 1/2 x 10 Photographs